U-KIM-1 as a predictor of treatment response in lupus nephritis. (January 2023) - Nozaki, Yuji; Shiga, Toshihiko; Ashida, Chisato; Tomita, Daisuke; Itami, Tetsu; Kishimoto, Kazuya; Kinoshita, Koji; Matsumura, Itaru
Objective: Biomarkers of disease activity in lupus nephritis (LN) are in demand. This is because they may be useful in patients who are unable to undergo invasive kidney biopsy, as predictors of renal function, and for early detection of LN recurrence. The focus is on the measurement of urinary chemokines and cytokines, especially in urinary biomarkers, which are non-invasive and simple. In our previous report, we reported that kidney injury molecule-1 (KIM-1) is expressed in injured tubules and that the number of tubular-KIM-expressing positive cells correlates with renal pathology findings and also with urinary (u)-KIM-1 levels. However, there have been no reports examining the effect of u-KIM-1 levels on response to therapy, correlation with renal pathology, and usefulness as a predictor of renal function. Methods: U-KIM-1 levels were measured by ELISA in 61 SLE patients. In 38 active LN who underwent renal biopsy, we also examined whether u-KIM-1 levels affected LN disease activity, renal histological findings, and predictors of renal function. Results: In SLE patients, proteinuria and u-KIM-1 levels were elevated in active LN compared to inactive LN. U-KIM-1 and proteinuria decreased with intensified treatment. U-KIM-1 levels also correlated with the percentage of glomerular crescent formation in renal pathology. In addition, patients with higher baseline u-KIM-1 levels had significantly higher eGFR and lower LN disease activity at 12 months after treatment intensification. Conclusions: These data suggest that u-KIM-1 levels correlate with LN disease activity and renal histopathology findings and may be used as a predictor of treatment response.